The Woman Reader in the “Feminine Press” of the XIX c. A Comparative Study between Biblioteca de señoritas [Ladies´ Library] (1858-1859) and La Mujer [Woman] (1878-1881) - Gil Medina, Cristina (Universidad Pedagógica y Tecnológica de Colombia, 2016)
In the mid XIX century, press in Colombia began to focus on a new type of reader: women. This initiative required a new outlook in the administration of periodical publications, evidenced in their materiality, contents, editorials, topics, writing genres, among other aspects. In this way, each publication accounted for the ideological orientation that guided it, and in this way, expressed a particular conception of woman, her role in society and consequently, the figure of ideal reader that it pretended to construct.